A Genetic Polymorphism of Interleukin 10 Gene at Position-1082 In Iraqis Patients with type 1 diabetes of - Ibtesam Badday Hassan; Azdihar Mohammed Jasem; Haneen Akram Habeeb (Al-Qadisiyah Journal of Pure Science, 2018)
The aim of this study was to evaluate the frequency of polymorphism of interleukin-10 Gene at position-1082 of the promoter region (IL-10-1082 SNP) in T1D and in healthy. The subjects were determined in 39 Iraqi patients, (12 males & 27 females; 1 5.65 Â± 1.79 years) and 21 controls (7 male and 14 female; 14.66 Â± 3.43 years) by polymerase chain reaction-specific sequence primer (PCR-SSP) assay, followed by electrophoresis on agarose-gel. The results revealed that comparing IL10 -1082 genotypes and alleles between T1D patients and controls it was observed that frequency of GA genotype was significantly higher (56.41vs. 42.85%; RR =23.7). may be considered as a risk factor for T1D While  A allele  was not significantly in patients contrast to controls, (41.03vs. 40.48%; RR =0.9)  and the associated EF values were 1.73and 1.02, respectively. In contrast, GG genotype and G allele (30.76vs. 58.97%, P =0.579 respectively) frequencies were significantly decreased in patients, compared to controls (38.09vs. 59.52%; P =1.000), and the associated PF values were 0.72 and 0.98, respectively . Similar observations were made in AA genotype. These findings suggest that IL10-1082 polymorphism showed associations (positive and negative) with T1D in the samples of Iraqi patients . Therefore,  the   functional   role  of  such  IL10-1082   might  have  been  altered  due  to  the  deviations  of  some  genotype  and  allele  frequencies.